THE INFLUENCE OF SOCIAL MEDIA INTERACTION AND DIGITAL PROMOTION ON TIKTOK ON ADIDAS PURCHASE DECISIONS AMONG GEN Z IN PALU CITY - Nurcaya Zahra; Zakiyah Zahara; Elimawaty Rombe; Setiawan Mandala Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of social media interactions through the TikTok Shop feature and digital promotions on purchasing decisions for Adidas products with brand awareness as an intervening variable among Generation Z in Palu City. The research method uses a quantitative approach with purposive sampling techniques and data processing through PLS-SEM 4.0. The results show that social media interactions and digital promotions have a positive and significant effect on brand awareness and purchasing decisions. Brand awareness also has a significant effect on purchasing decisions and mediates the relationship between social media interactions and digital promotions on purchasing decisions. These findings confirm that interaction-based promotional strategies and creative content on TikTok are effective in increasing brand awareness and driving consumer purchasing decisions.